Perceived Stress, Depressive Symptoms, and Oxidative DNA Damage. Issue 1 (January 2018) - Shimanoe, Chisato; Hara, Megumi; Nishida, Yuichiro; Nanri, Hinako; Horita, Mikako; Yamada, Yosuke; Li, Yun-Shan; Kasai, Hiroshi; Kawai, Kazuaki; Higaki, Yasuki; Tanaka, Keitaro
ABSTRACT: Objective: Psychosocial stress may influence the risk of disease through its association with oxidative DNA damage. We examined whether perceived stress and depressive symptoms were associated with urinary excretion of 8-hydroxydeoxyguanosine (8-OHdG), with mutual interaction on 8-OHdG. Methods: This cross-sectional study included 6517 individuals aged 45 to 74 years who participated, between 2010 and 2012, in a follow-up survey of an ongoing cohort study. Perceived stress during the past year was measured using a self-report questionnaire. Depressive symptoms were evaluated using the Zung Self-Rating Depression Scale. Urinary 8-OHdG concentrations were measured using a column switching high-pressure liquid chromatography system coupled to an electrochemical detector. Results: Higher perceived stress was significantly associated with higher 8-OHdG (2.1% increase per one-category increase of stress; p trend = .025), even after adjusting for sex, age, supplement use, psychosocial factors, psychotropic medication use, smoking, and body mass index. This association was modestly attenuated after further adjustment for physical activity, suggesting possible mediation or confounding by this factor. Depressive symptoms were not significantly associated with 8-OHdG. No significant interaction was detected between perceived stress and depressive symptoms on 8-OHdG. Conclusions: In a general Japanese population, we found a weak positive association between perceived stress and urinary excretion of 8-OHdG, whereas no association was observed between depressive symptoms and 8-OHdG. Further studies are needed to examine whether the association between perceived stress and 8-OHdG is modified by depressive symptoms. Abstract : Supplemental digital content is available in the text.